Impact of auditory environments on language outcomes in children with a cochlear implant. - Poupore, Nicolas S.; Chidarala, Shreya; Morris, Nevitte S.; McRackan, Theodore R.; Schvartz-Leyzac, Kara C. (International Journal of Audiology, 2024)
To analyse the effects of auditory environments on receptive and expressive language outcomes in children with a CI. A single-institution retrospective review was performed. The auditory environments included Speech-Noise, Speech-Quiet, Quiet, Music, and Noise. Hearing Hour Percentage (HHP) and percent total hours were calculated for each environment. Generalised Linear Mixed Models (GLMM) analyses were used to study the effects of auditory environments on PLS Receptive and Expressive scores. Thirty-nine children with CI On GLMM, an increase in Quiet HHP and Quiet percent total hours were positively associated with PLS Receptive scores. Speech-Quiet, Quiet, and Music HHP were positively associated with PLS Expressive scores, with only Quiet being significant for percent total hours. In contrast, percent total hours of Speech-Noise and Noise had a significant negative association with PLS Expressive scores. This study suggests that more time spent in a quiet auditory environment positively influences PLS Receptive and Expressive scores and that more time listening to speech in quiet and music positively influences PLS Expressive scores. Time spent in environments recognised as Speech-Noise and Noise might negatively impact a child's expressive language outcomes with a CI. Future research is needed to better understand this association.